Determination of linuron in chamomile by LC-MS/MS using the QuEChERS extraction method - Špirović Trifunović, Bojana D.; Vuković, Gorica Lj.; Jovanović–Radovanov, Katarina D.; Bursić, Vojislava P.; Meseldžija, Maja U. (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Linuron is a selective herbicide used for the control of broadleaf weeds. Its mode of action is the inhibition of photosynthesis. The QuEChERS method for extraction of linuron residues from chamomile was used. The LC–MS/MS method was used for determination of linuron residues. Its linearity was studied in a range of 0.025-0.50 μg/ml using matrix-matched calibration, and the determination coefficient (R2) was higher than 0.99. Blank chamomile samples were spiked with linuron solution at three concentration levels yielding recoveries of over 90%. The internal standard added in all samples was isoproturon–d6. There were no linuron residues in chamomile flowers, while the residues ranged from 0.010 to 0.040 mg/kg in the flower stalk samples.